2014
DOI: 10.5897/jma2013.0286
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the antimicrobial and hemolytic activity of venom of some Egyptian scorpion

Abstract: Leuirus quinquestriatus, Androctonus amoreuxi and Androctonus australis are venomous scorpion in Egypt. Their venom is complex mixture of salts, neurotoxins, peptides and proteins which has therapeutic applications, and can rapidly kill a broad range of microbes. Estimations of total proteins of the venom indicated that L. quinquestriatus had the highest value than the others (10.64 ± 0.04). Hemolytic activity of human erythrocytes was detected and showed that all concentrations (20, 8 and 5 mg/ml) of tested s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…They showed that L. quinquestriatus venom had a significant antibacterial effect against B. subtillis and C. freundi. In contrast, A. amoreuxi and A. australis venoms did not have a noticeable effect on the tested bacteria [24].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…They showed that L. quinquestriatus venom had a significant antibacterial effect against B. subtillis and C. freundi. In contrast, A. amoreuxi and A. australis venoms did not have a noticeable effect on the tested bacteria [24].…”
Section: Discussionmentioning
confidence: 62%
“…They showed that the scorpion venoms significantly inhibited the growth of S. Aureus, Proteus mirabilis, Proteus vulgaris, Enterobacter aerogenes, Pseudomonas aeruginosa and E. Coli bacteria [6]. Salama and Geasa studied the antimicrobial activity of venoms from three Egyptian scorpions (Leuirus quinquestriatus, Androctonus amoreuxi and Androctonus australis) [24]. In their study, the antimicrobial activities of these venoms against four Gram-positive and Gram-negative bacteria (Bacillus cereus, Bacillus subtillis, Citrobacter freundi and Klibsella pneumonia) were evaluated.…”
Section: Discussionmentioning
confidence: 99%